Combined Source-Channel Coding of Images under Power and Bandwidth Constraints - Raja, Nouman; Xiong, Zixiang; Fossorier, Marc (EURASIP journal on advances in signal processing, 2007)
This paper proposes a framework for combined source-channel coding for a power and bandwidth constrained noisy channel. The framework is applied to progressive image transmission using constant envelope M -ary phase shift key (M-PSK) signaling over an additive white Gaussiannoise channel. First, the framework is developed for uncoded M-PSK signaling (with M =2k). Then, it is extended to include coded M-PSK modulation using trellis coded modulation (TCM). An adaptive TCM system is also presented. Simulation results show that, depending on the constellation size, coded M-PSK signaling performs 3.1 to 5.2 dB better than uncoded M-PSK signaling. Finally, the performance of our combined source-channel coding scheme is investigated from the channel capacity point of view. Our framework is further extended to include powerful channel codes like turbo and low-density parity-check (LDPC) codes. With these powerful codes, our proposed scheme performs about one dB away from the capacity-achieving SNR value of the QPSK channel.